The Primacy of the Public - Schultz-Bergin, Marcus (Open textbook library., 2021)
The Primacy of the Public presents a framework for engineering and technology ethics focused around three core ethical principles: the principle of welfare, the autonomy principle, and the fairness principle. To support this framework, the book begins with an examination of multiple perspectives we may take on engineering and technology, all of which support the centrality of ethical analysis and evaluation. These include the nature of engineering as a profession, the social context of engineering and technology, and the view that many technologies constitute social experiments.